Analysis of Problem Solving on IDEAL Problem Solving Learning Based on Van Hiele Theory Assisted by Geogebra on Geometry - Abduh, M. Faisal; Waluya, S. B.; Mariani, Scolastika (Unnes Journal of Mathematics Education Research, 2020)
The objectives of this study are to analyze the effectiveness of the learning of IDEAL Problem Solving models based on Van Hiele theory assisted by Geogebra software and to describe students’ problem solving ability at each level of geometrical thinking. This research was a type of qualitative and quantitative combination research. The combination model of this study was the type of concurrent triangulation, the combination of qualitative and quantitative methods in a balanced way. Quantitative research sampling technique was simple random sampling in which this study was taken in one experimental class and one control class. The technique of selecting qualitative research subjects was non-probability sampling, where the taking of subjects was based on the level of geometrical thinking. The conclusions are obtained (1) IDEAL Problem solving models Learning based on van Hiele theory assisted by Geogebra software is effective on students' problem solving ability. (2) The problem solving ability of each level of Van Hiele's geometry thinking is that students at level 1 (analysis), they can understand the problem but cannot plan their solution well. Level 2 students (informal deduction), they can understand problems, plan, implement plans well, but they cannot check results. Level 3 (deduction), the students can understand problems, plan, implement plans, and check results well.